2013
DOI: 10.1007/s00701-013-1851-5
|View full text |Cite
|
Sign up to set email alerts
|

Paradox in the cubital tunnel syndrome—frequent involvement of left elbow: first report

Abstract: Profound involvement with cubital tunnel was found in left elbow. According to the finding of non-dominant elbow involvement in our study, the exact etiology and ideal management of cubital tunnel syndrome continues to be heavily debated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 15 publications
1
6
0
1
Order By: Relevance
“…In this study the syndrome was present in 57% of women and affected the left side in 62%. Kamat et al (2014) and Jeon et al (2010) confirmed that the syndrome was more prevalent in women and Kanat et al (2014) confirmed that it involved primarily the upper left limb. Perhaps this is the consequence of women, undertaking jobs previously performed by men.…”
Section: Discussionmentioning
confidence: 67%
“…In this study the syndrome was present in 57% of women and affected the left side in 62%. Kamat et al (2014) and Jeon et al (2010) confirmed that the syndrome was more prevalent in women and Kanat et al (2014) confirmed that it involved primarily the upper left limb. Perhaps this is the consequence of women, undertaking jobs previously performed by men.…”
Section: Discussionmentioning
confidence: 67%
“…If indeed one is the first to report something and that something is of value. [ 11 12 ] In addition, the knowledge provided in the present study is useful and will widen the anthropometric knowledge of humanity. Preferred hand use has been observed even at embryonic and fetal stages in humans, long before language ability is developed.…”
Section: Discussionmentioning
confidence: 88%
“…The recognition of this fact is important, if indeed one is the first to report something and that something is of value. [ 18 27 28 29 ] Given the high frequency of sudden death following SAH, it is important for intensive care physicians to become familiar with their pathophysiology, allowing for more prompt and appropriate treatment of SAH patients. In some contexts, red flags mean that something important needs to be brought to immediate attention.…”
Section: Discussionmentioning
confidence: 99%